2014
DOI: 10.1002/cmdc.201402209
|View full text |Cite
|
Sign up to set email alerts
|

Small Alterations in Cobinamide Structure Considerably Influence sGC Activation

Abstract: Specially designed B-ring-modified cobalamin derivatives were synthesized and tested as potential activators of soluble guanylyl cyclase (sGC). Herein, we disclose the influence of substituents at the c- and d-positions in hydrophilic and hydrophobic cobyrinic acid derivatives on their capacities to activate sGC. The presence of the amide group at c-/d-position in cobyrinic acid derivatives strongly influence the level of sGC activation. Removal of the d-position altogether has a profound effect for hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…54,55 In a related but distinct strategy for developing B 12 -based therapeutics, the design of dysfunctional B 12 analogues encounters an encouraging renaissance and aims toward the development of new classes of antibacterial and antiproliferative agents (chapter 2.3). [60][61][62] In all four approaches, the basic properties of B 12 are explored for obtaining compounds with new behaviour and functions. [60][61][62] In all four approaches, the basic properties of B 12 are explored for obtaining compounds with new behaviour and functions.…”
Section: Recent Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 In a related but distinct strategy for developing B 12 -based therapeutics, the design of dysfunctional B 12 analogues encounters an encouraging renaissance and aims toward the development of new classes of antibacterial and antiproliferative agents (chapter 2.3). [60][61][62] In all four approaches, the basic properties of B 12 are explored for obtaining compounds with new behaviour and functions. [60][61][62] In all four approaches, the basic properties of B 12 are explored for obtaining compounds with new behaviour and functions.…”
Section: Recent Trendsmentioning
confidence: 99%
“…In particular, they showed that `incomplete` corrinoids such as dicyanocobinamide 1-CN (Figure 4) operate as activators of soluble guanylyl cyclase (sGC), thus offering tremendous potential for the treatment of various `NO/3`,5`-cyclic guanosine monophosphate (cGMP) signalling pathway-related diseases`. 60,192 For example, introducing significant changes into the B-ring area of compound 15 (Figure 15) improves the activity by almost 15 % and reduces the effective concentration by a third (12 µM) compared to 1-CN. 32, 189 Surprisingly, it was found that the natural porphyrinoids protoporphyrin IX and dicyanocobinamide (1-CN; Figure 4) behave as activators of sGC.…”
Section: Corrinoids As Enzyme Activatorsmentioning
confidence: 99%
“…Detailed recognition of the nature of its interactions with axial ligands as well as biopolymers, particularly transport proteins, has raised a rapid growth of interest in B 12 -inspired compounds in the context of diverse biomedical applications [ 4 ]. Hence, it is used as cyanide detecting [ 5 ] and detoxifying agent [ 6 ], and an increasing number of derivatives are applied as anti-vitamins in the regulation of pathological biochemical processes [ 7 ] or as activators of enzymes, e.g., guanylyl cyclase [ 8 ]. During the last several years, the concept of using cyanocobalamin as a carrier of agents used in targeted diagnostics and therapy, has also been strongly developed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%